THE IMPACT OF THE COVID-19 PANDEMIC ON COMPREHENSIVE INCOME OF AUTOMOTIVE INDUSTRY COMPANIES AND COMPONENTS LISTED IN INDONESIA STOCK EXCHANGE - Aliah, Nur (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2021)
This study aims to determine the impact of the Covid-19 pandemic on the profit and loss of automotive and component industrial companies. The variables used in this study are comprehensive income before the Covid-19 pandemic, namely 2019 and comprehensive income during the Covid-19 pandemic, namely 2020 in the company's financial statements for the first quarter, second quarter and third quarter. The sample of this research is companies engaged in the automotive industry and components that are listed on the Indonesia Stock Exchange and have financial reports for the first to third quarter of 2019 to 2020. The research sample was selected using the purposive sampling method and obtained 14 companies with The number of observations was 42 samples, namely the income statement for the first, second, third quarter 2019 and 2020. Hypothesis testing was carried out using analysisWilcoxon Signed Ranks Test. The result of this research is that the Covid-19 pandemic affects the comprehensive income of automotive and component industrial companies.